Disconnected Duct Syndrome: Refractory Inflammatory External Pancreatic Fistula Following Percutaneous Drainage of an Infected Peripancreatic Fluid Collection. A Case Report and Review of the Literature - Solanki, Rashesh; Koganti, Suman Bhushan; Bheerappa, Nagari; Sastry, Regulagedda Adikeshava (JOP. Journal of the Pancreas, 2011)
Context Inflammatory external pancreatic fistulas behave differently from postoperative external pancreatic fistulas in that the former are less likely to close without intervention and take a longer time to do so. The principal determinants of closure of an external pancreatic fistula are the anatomy of the fistulous tract (end versus side, main duct versus side branch), the presence of downstream ductal obstruction, ongoing peripancreatic inflammation and etiology of the fistula (inflammatory versus postoperative). While the approach to diagnosis and management of postoperative pancreatic fistulas has been standardized, the same is lacking for inflammatory external pancreatic fistulas, partly due to the absence of a unifying definition of the latter and a paucity of data on the topic. Case report We report the case of disconnected duct syndrome, an end inflammatory fistula, following percutaneous drainage of an infected pancreatic fluid collection with two failed attempts at endoscopic treatment, treated successfully by surgery, and we also attempted to review the literature on the topic. Conclusions “Disconnected duct syndrome”, an end inflammatory fistula, following percutaneous or surgical treatment of severe acute pancreatitis is a distinct entity as spontaneous closure is exceedingly uncommon. Surgery is almost always required and is successful in the majority of cases. Image: CECT abdomen showing a large intrapancreatic fluid collection extending into the hepatogastric ligament.